Effect of dexamethasone on complications or all cause mortality after major non-cardiac surgery: multicentre, double blind, randomised controlled trial. (2nd June 2021) - Asehnoune, Karim; Le Moal, Charlene; Lebuffe, Gilles; Le Penndu, Marguerite; Josse, Nolwen Chatel; Boisson, Matthieu; Lescot, Thomas; Faucher, Marion; Jaber, Samir; Godet, Thomas; Leone, Marc; Motamed, Cyrus; et al.
Abstract: Objective: To assess the effect of dexamethasone on complications or all cause mortality after major non-cardiac surgery. Design: Phase III, randomised, double blind, placebo controlled trial. Setting: 34 centres in France, December 2017 to March 2019. Participants: 1222 adults (>50 years) requiring major non-cardiac surgery with an expected duration of more than 90 minutes. The anticipated time frame for recruitment was 24 months. Interventions: Participants were randomised to receive either dexamethasone (0.2 mg/kg immediately after the surgical procedure, and on day 1) or placebo. Randomisation was stratified on the two prespecified criteria of cancer and thoracic procedure. Main outcomes measures: The primary outcome was a composite of postoperative complications or all cause mortality within 14 days after surgery, assessed in the modified intention-to-treat population (at least one treatment administered). Results: Of the 1222 participants who underwent randomisation, 1184 (96.9%) were included in the modified intention-to-treat population. 14 days after surgery, 101 of 595 participants (17.0%) in the dexamethasone group and 117 of 589 (19.9%) in the placebo group had complications or died (adjusted odds ratio 0.81, 95% confidence interval 0.60 to 1.08; P=0.15). In the stratum of participants who underwent non-thoracic surgery (n=1038), the primary outcome occurred in 69 of 520 participants (13.3%) in the dexamethasone group and 93 of 518 (18%) in the placebo group (adjusted odds ratio 0.70, 0.50 to 0.99). Adverse events were reported in 288 of 613 participants (47.0%) in the dexamethasone group and 296 of 609 (48.6%) in the placebo group (P=0.46). Conclusions: Dexamethasone was not found to significantly reduce the incidence of complications and death in patients 14 days after major non-cardiac surgery. The 95% confidence interval for the main result was, however, wide and suggests the possibility of important clinical effectiveness. Trial registration: ClinicalTrials.gov NCT03218553 .